Listening To Grasshoppers : Field Notes On Democracy - Roy, Arundhati (Rawalpindi Services Book Club, 2011)
What happens once democracy has been used up? When it has been hollowed out and emptied of meaning? This title provides an exploration of the political picture in India.
Keywords: Listening To Grasshoppers : Field Notes On Democracy -- Social Science -- Politics and government -- Nationalism